2020
DOI: 10.1152/ajpcell.00550.2019
|View full text |Cite
|
Sign up to set email alerts
|

Insulin does not stimulate β-alanine transport into human skeletal muscle

Abstract: To test whether high circulating insulin concentrations influence the transport of β-alanine into skeletal muscle at either saturating or subsaturating β-alanine concentrations, we conducted two experiments whereby β-alanine and insulin concentrations were controlled. In experiment 1, 12 men received supraphysiological amounts of β-alanine intravenously (0.11 g·kg−1·min−1 for 150 min), with or without insulin infusion. β-Alanine and carnosine were measured in muscle before and 30 min after infusion. Blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
0
11
0
6
Order By: Relevance
“…It is likely that these large amounts of BA are required because the incorporation of ingested BA into the muscle is very low, with ∼3-6% of ingested BA estimated to contribute toward MCarn accumulation (Stegen et al, 2013;Blancquaert et al, 2015). BA uptake into the muscle seems to be rapid and efficient, however the ability of carnosine synthase to incorporate it into MCarn is far slower (Bakardjiev and Bauer, 1994;de Souza Goncalves et al, 2020) and so the remaining BA is likely to be converted toward other processes such as transamination or oxidation (Blancquaert et al, 2016). Despite this inefficiency in the use of supplemental BA to synthesize MCarn, very large increases, to the order of 200%, have been reported (Saunders et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that these large amounts of BA are required because the incorporation of ingested BA into the muscle is very low, with ∼3-6% of ingested BA estimated to contribute toward MCarn accumulation (Stegen et al, 2013;Blancquaert et al, 2015). BA uptake into the muscle seems to be rapid and efficient, however the ability of carnosine synthase to incorporate it into MCarn is far slower (Bakardjiev and Bauer, 1994;de Souza Goncalves et al, 2020) and so the remaining BA is likely to be converted toward other processes such as transamination or oxidation (Blancquaert et al, 2016). Despite this inefficiency in the use of supplemental BA to synthesize MCarn, very large increases, to the order of 200%, have been reported (Saunders et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas TauT is a high-specificity, low capacity β-alanine transporter (which needs to be coupled with a Na and Cl ions) [ 75 ] and likely saturated at high concentration of systemic β-alanine, PAT1, on the contrary, is a low-specificity, high-capacity transporter probably less saturable. Although some studies have suggested that TauT plays a dominant role in β-alanine muscle cell uptake, it has also been suggested the existence of additional uptake mechanisms: after intravenous infusion of β-alanine at saturable level, exceeding the maximum transport capacity of TauT in humans a 2.5–3-fold increase in muscle β-alanine was achieved compared to a 1.5-fold increase when sub-saturating amounts were administered [ 43 ]. This would support the idea that higher concentrations would achieve greater muscle uptake, even beyond the transport capacity of TauT.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise. Another study showed that paresthesia intensity was already decreasing albeit higher concentrations (~4-fold) were reached at later time points after intravenous infusion [ 43 ]. This behavior is similar to the one found in the current study and supports the findings that paresthesia intensity is not well correlated with plasma peak concentration, it is highly variable and tolerance may be developed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations